2000
DOI: 10.1074/jbc.m001507200
|View full text |Cite
|
Sign up to set email alerts
|

Cation Hexaammines Are Selective and Potent Inhibitors of the CorA Magnesium Transport System

Abstract: The chemistry of Mg 2ϩ is unique among the biologically relevant cations. Compared with calcium, potassium, and sodium, Mg 2ϩ possesses the largest hydrated radius, the smallest ionic radius, and the greatest charge density (1). Its volume change from hydrated to atomic cation is almost 400-fold, whereas Ca 2ϩ , Na ϩ , and K ϩ are only 25-, 25-, and 4-fold, respectively. Waters of hydration are bound 3-4 orders of magnitude more tightly to Mg 2ϩ than to other common biological cations. The geometry of the hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(75 citation statements)
references
References 31 publications
2
73
0
Order By: Relevance
“…The inhibition of uptake of 10 mM nickel chloride by both hexa-ammine cobalt (III) chloride and magnesium ions is consistent with CorA involvement. However, hexa-ammine cobalt (III) chloride inhibition was modest compared with that reported for the Salmonella CorA (Kucharski et al, 2000). The abolition of hydrogenase activity in the cj1584c mutant after growth in media with no added nickel indicates that uptake through the ABC system is essential for hydrogenase synthesis at low environmental nickel concentrations (as is likely in the natural gut environment), but the activity of the alternative low-affinity systems during growth with excess nickel is sufficient to restore hydrogenase activity to wild-type levels.…”
Section: Discussionmentioning
confidence: 89%
“…The inhibition of uptake of 10 mM nickel chloride by both hexa-ammine cobalt (III) chloride and magnesium ions is consistent with CorA involvement. However, hexa-ammine cobalt (III) chloride inhibition was modest compared with that reported for the Salmonella CorA (Kucharski et al, 2000). The abolition of hydrogenase activity in the cj1584c mutant after growth in media with no added nickel indicates that uptake through the ABC system is essential for hydrogenase synthesis at low environmental nickel concentrations (as is likely in the natural gut environment), but the activity of the alternative low-affinity systems during growth with excess nickel is sufficient to restore hydrogenase activity to wild-type levels.…”
Section: Discussionmentioning
confidence: 89%
“…The Asn-ring, because of its geometry, apparently allows the entry of only partially hydrated Mg 2+ . Additionally, the Asn-ring might be the binding area for cobalt(III)hexamine, the known inhibitor of CorA proteins (16), which could tightly seal the selectivity filter (Fig. S3).…”
Section: Resultsmentioning
confidence: 99%
“…In a recent computational study (22), removal of the ten regulatory ions from M1 and M2 led to changes in the tilt of α7, resulting in an iris-like dilation of the pore and subsequent hydration of the hydrophobic pore region between M302 and M291 (MM stretch), suggesting an allosteric mechanism coupling intracellular Mg 2+ concentration to hydrophobic gating. It has been further suggested that the acidic electrostatic nature of α5 and α6 might be used to change the position of the basic sphincter, which surrounds the tightest pore constriction formed by M291 (17 (23). NMR studies on an isolated TM domain (24) report weak and dynamic binding of hydrated Mg 2+ and [Co(NH 3 ) 6 ] 3+ to the periplasmic α7-α8 loop.…”
mentioning
confidence: 99%